2021
DOI: 10.1101/2021.04.06.438709
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibodies to the SARS-CoV-2 receptor-binding domain that maximize breadth and resistance to viral escape

Abstract: An ideal anti-SARS-CoV-2 antibody would resist viral escape, have activity against diverse SARS-related coronaviruses, and be highly protective through viral neutralization and effector functions. Understanding how these properties relate to each other and vary across epitopes would aid development of antibody therapeutics and guide vaccine design. Here, we comprehensively characterize escape, breadth, and potency across a panel of SARS-CoV-2 antibodies targeting the receptor-binding domain (RBD), including S3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 88 publications
1
29
0
Order By: Relevance
“…RBD-based immunogens in various oligomeric states have been investigated as genetic or protein-based vaccines for SARS-CoV-2, including monomers (27)(28)(29)(30)(31), dimers (32), trimers (33)(34)(35) and highly multivalent nanoparticles (25,(36)(37)(38)(39), several of which are now being evaluated in clinical trials. Although the RBD comprises only a minority of the total mass and antigenic surface of S and could in principle be more susceptible to escape mutations, this theoretical disadvantage may be mitigated by both functional constraints and the elicitation of antibodies targeting multiple distinct neutralizing epitopes in the RBD by infection or vaccination (25,(40)(41)(42)(43). Indeed, the vast majority of neutralizing activity elicited by SARS-CoV-2 infection and currently approved S-based vaccines targets the RBD (40,(44)(45)(46)(47)(48), as do most clinical-stage monoclonal antibodies (49).…”
Section: Introductionmentioning
confidence: 99%
“…RBD-based immunogens in various oligomeric states have been investigated as genetic or protein-based vaccines for SARS-CoV-2, including monomers (27)(28)(29)(30)(31), dimers (32), trimers (33)(34)(35) and highly multivalent nanoparticles (25,(36)(37)(38)(39), several of which are now being evaluated in clinical trials. Although the RBD comprises only a minority of the total mass and antigenic surface of S and could in principle be more susceptible to escape mutations, this theoretical disadvantage may be mitigated by both functional constraints and the elicitation of antibodies targeting multiple distinct neutralizing epitopes in the RBD by infection or vaccination (25,(40)(41)(42)(43). Indeed, the vast majority of neutralizing activity elicited by SARS-CoV-2 infection and currently approved S-based vaccines targets the RBD (40,(44)(45)(46)(47)(48), as do most clinical-stage monoclonal antibodies (49).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, S309, a class 3 anti-RBD antibody isolated from a SARS-CoV-infected donor, demonstrated cross-reactive neutralization of SARS-CoV-2 (Pinto et al, 2020). Furthermore, reports of class 4 human antibodies that exhibit cross-reactive binding and neutralization amongst sarbecoviruses Starr et al, 2021a;Tortorici et al, 2021) suggest that further investigation of antibodies from COVID-19 convalescent donors could lead to discoveries of potent and broadly cross-reactive class 4 antibodies that recognize the highly-conserved, 'cryptic' RBD epitope.…”
Section: Introductionmentioning
confidence: 99%
“…Starr et al discovered antibodies that target conserved, functionally constrained RBD residues. One of these, S2H97, showed high affinity and neutralization breadth across SARS-CoV-2-related sarbecoviruses [80]. An accompanying study showed that S2X259, which binds to a highly conserved cryptic RBD epitope, crossneutralized all the VOCs and a wide spectrum of human and zoonotic sarbecoviruses.…”
Section: Neutralizing Antibodiesmentioning
confidence: 99%